Ruch Stu – alternatywa dla klasy politycznej powstałej w 1989 roku - Borowiec, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2003)
The Movement of a Hundred (Polish: Ruch Stu) was to become an alternative for the political class that emerged after 1989. The whole political class was supposed to be substituted in a democratic manner by new people entering the political arena. The minimum political platform was to unite the activists of diversified political provenience. The Movement of a Hundred was to provide a new way of functioning for the political parties. The very naming of the party as the „movement”, that is a common activity of new people, was of significant importance itself. They were to introduce a new quality of politics and a new model of a politician. Current political events in- volved the Movement of a Hundred in a never-ending spiral of political elections. The two most important events were supporting Lech Wa³êsa before the presidential elec- tions and the decision to join the structures of the AWS (Solidarity Election Action). The Movement of a Hundred was to be an alternative and novelty on the Polish political arena. However, it became a tiny, hardly observable, component of the right wing of the former political class. It was commonly known to have been incorporated by the old elite. The Movement of a Hundred adopted behavioral models that were typical of a former political class (including the conflicts between the leaders), as well as the heavily criticized faults (struggle for gaining influence in the AWS) that resulted in the collapse of the whole right wing in the next parliamentary elections.
The Movement of a Hundred - an Alternative for the Political Class Emerged in 1989